2001
DOI: 10.1128/jvi.75.21.10326-10333.2001
|View full text |Cite
|
Sign up to set email alerts
|

cdc2 Cyclin-Dependent Kinase Binds and Phosphorylates Herpes Simplex Virus 1 U L 42 DNA Synthesis Processivity Factor

Abstract: Earlier studies have shown that cdc2 kinase is activated during herpes simplex virus 1 infection and that its activity is enhanced late in infection even though the levels of cyclin A and B are decreased below levels of detection. Furthermore, activation of cdc2 requires the presence of infected cell protein no. 22 and the U L 13 protein kinase, the same gene products required for optimal expression of a subset of late genes exemplified by U S 11, U L 38, and U L 41. The possibility that the activation of cdc2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 35 publications
2
27
1
Order By: Relevance
“…Rosco is highly selective in that among 68 proteins tested, it inhibited only CDK1, CDK2, CDK5, and CDK7 with high potency and DYRK1a, ERK1 and ERK2 with lower potency (recently reviewed in reference 70). Based on independent evidence, two of the Rosco-sensitive CDKs, CDK1 and CDK2, have been postulated to be required for HSV-1 transcription (2,3,71,73), both these CDKs are also inhibited by IFN-␣. Since the human genome encodes 518 potential protein kinases (47) and numerous other ATP-binding proteins, however, it is impossible to conclude from the experiments described in this paper which specific kinases are required for activation of HSV-1 transcription and inhibited by Rosco.…”
Section: Discussionmentioning
confidence: 99%
“…Rosco is highly selective in that among 68 proteins tested, it inhibited only CDK1, CDK2, CDK5, and CDK7 with high potency and DYRK1a, ERK1 and ERK2 with lower potency (recently reviewed in reference 70). Based on independent evidence, two of the Rosco-sensitive CDKs, CDK1 and CDK2, have been postulated to be required for HSV-1 transcription (2,3,71,73), both these CDKs are also inhibited by IFN-␣. Since the human genome encodes 518 potential protein kinases (47) and numerous other ATP-binding proteins, however, it is impossible to conclude from the experiments described in this paper which specific kinases are required for activation of HSV-1 transcription and inhibited by Rosco.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, it has been shown that the expression of glycoprotein C and U S 11 is enhanced by the ICP22-mediated interaction of the viral DNA processivity factor U L 42 (a viral functional homologue of proliferating cell nuclear antigen), cyclin-dependent kinase cdc2, and topoisomerase IIa (34)(35)(36). One hypothesis that could explain the mechanism of activation of late promoters and the role of ionizing radiation in inducing these promoters is that these are activated by modifications in the structure of the DNA, either as a result of nicks, gaps, or other perturbations in the DNA structure.…”
Section: Discussionmentioning
confidence: 99%
“…The construction of a U L 42-expressing plasmid in the multiple coding site of pcDNA3.1(ϩ) has been described elsewhere (7). A plasmid encoding HA-tagged dn cdc2 (cdc2-dn-HA) kinase was provided by S. van den Heuvel (Massachusetts General Hospital Cancer Center, Charlestown, MA) (22).…”
Section: Methodsmentioning
confidence: 99%
“…Immunoprecipitation with antibody to U L 42 was done as described (7). The electrophoretically separated proteins in the precipitate were reacted with antibodies to topoisomerase II␣ and U L 42.…”
Section: Methodsmentioning
confidence: 99%